Acute exacerbations in the INPULSIS trials of nintedanib in idiopathic pulmonary fibrosis. Issue 5 (19th May 2017) - Collard, Harold R.; Richeldi, Luca; Kim, Dong Soon; Taniguchi, Hiroyuki; Tschoepe, Inga; Luisetti, Maurizio; Roman, Jesse; Tino, Gregory; Schlenker-Herceg, Rozsa; Hallmann, Christoph; du Bois, Roland M.
Time to first investigator-reported acute exacerbation was a key secondary end-point in the INPULSIS trials of nintedanib in patients with idiopathic pulmonary fibrosis (IPF). We used the INPULSIS trial data to investigate risk factors for acute exacerbation of IPF and to explore the impact of nintedanib on risk and outcome of investigator-reported and adjudicated confirmed/suspected acute exacerbations. Mortality following these events and events adjudicated as not acute exacerbations was analysed using the log rank test. Risk of acute exacerbations was most strongly associated with the following variables: baseline forced vital capacity (higher risk with lower value), baseline supplemental oxygen (higher risk with use), baseline antacid medication (higher risk with use), treatment (higher risk with placebo), and for confirmed/suspected acute exacerbations, cigarette smoking. Mortality was similar following investigator-reported and adjudicated confirmed/suspected acute exacerbations. Nintedanib had no significant effect on risk of mortality post-exacerbation. Investigator-reported acute exacerbations of IPF are associated with similar risk factors and outcomes as adjudicated confirmed/suspected acute exacerbations. Investigator-reported and confirmed/suspected acute exacerbations of IPF have similar risk factors and outcomes http://ow.ly/k1Sj309SZSf